Fatigue behavior of removable partial denture cast and laser‐sintered cobalt‐chromium (CoCr) and polyetheretherketone (PEEK) clasp materials - Jenny Zheng; John M. Aarts; Sunyoung Ma; John N. Waddell; Joanne J. E. Choi (Wiley, 2022)
Abstract Objective To investigate the fatigue behavior of cast and laser‐sintered cobalt‐chromium (CoCr) and polyetheretherketone (PEEK) material for a removable partial denture (RPD) clasps. Methods Dumbbell‐shaped specimens were digitally designed with the center part of the dumbbell being a half‐round shape at the cross‐sectional dimension of 1.25 mm to simulate a typical clasp design and dimensions. A fatigue machine with an offset axis rotation system simulated a typical undercut depth of 0.25, 0.50, and 0.75 mm. Each group was subjected to 30,000 fatigue cycles (simulating 21 years) or till specimen failure. Before testing, the stress value at each undercut depth for each specimen was established in a universal testing machine and SN curves were plotted for each group. Data were statistically analyzed using Kruskal-Wallis and post hoc tests. The fractured surfaces were analyzed using SEM. Results The average fatigue cycles with 0.25, 0.50, and 0.75 mm undercuts were 27,155 ± 6277, 9298 ± 4033, 5642 ± 8785 for cast CoCr and 26,765 ± 6150, 11,318 ± 7931, 2861 ± 4803, for laser‐sintered CoCr, respectively. Apart from three specimens, the PEEK groups did not fail during the simulation period. Clasps with 0.25 mm deflection showed significantly higher fatigue resistance than other groups (p < .001). There was no significant difference in fatigue behavior between the cast and laser‐sintered CoCr. Microporosities at the fractured site along with irregular crack propagation were observed for cast and laser‐sintered CoCr specimens. Fatigue‐induced broken polymer crosslinking chains were observed in PEEK specimens. Conclusion PEEK material exhibited the highest fatigue resistance and significantly lower deflection resistance. Cast and laser‐sintered CoCr showed similar fatigue resistance and behavior.